2020
DOI: 10.21203/rs.3.rs-35515/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study on lesions of reproductive disorders of cows and female dromedary camels slaughtered at Addis Ababa, Adama and Akaki abbatoirs with bacterial isolation and characterization

Abstract: Background Reproduction is a basic prerequisite to efficient livestock production. The reproductive performance depends upon the normal structure and functions of genital organs. Methods A cross-sectional study design was conducted from November 2016 to May 2017 to identify and compare the frequency of reproductive organ pathological lesions and to isolates bacteria associated with uterine lesions in female dromedary camels and cows slaughtered at Addis Ababa and Adama municipal abattoirs and Akaki slaughter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
8
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(17 citation statements)
references
References 27 publications
(39 reference statements)
8
8
1
Order By: Relevance
“…In agreement with this study, various pathological lesions such as endometritis, pyosalphix, uterine tumor, ovarian hypoplasia, salpingitis, paraovarian cyst, and endometrial congestion with different degrees of severity in reproductive organs of female camels were reported in previous studies [40,42,43]. According to the current study, occurrences and distribution of gross pathological lesions varied among reproductive organs of she-camels where significantly the highest proportion (41.2%; p � 0.00) was observed in the uterus followed by the ovary (35.3%).…”
Section: Postmortem Findings and Lesion Characterizationsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with this study, various pathological lesions such as endometritis, pyosalphix, uterine tumor, ovarian hypoplasia, salpingitis, paraovarian cyst, and endometrial congestion with different degrees of severity in reproductive organs of female camels were reported in previous studies [40,42,43]. According to the current study, occurrences and distribution of gross pathological lesions varied among reproductive organs of she-camels where significantly the highest proportion (41.2%; p � 0.00) was observed in the uterus followed by the ovary (35.3%).…”
Section: Postmortem Findings and Lesion Characterizationsupporting
confidence: 92%
“…ough it is difficult to determine the exact cause of ovarian follicular cysts, it can be realized that they develop when one or more follicles fail to ovulate and subsequently fail to regress maintaining growth and steroidogenesis [40,53,54]. In partial agreement to our study, in the work of Benaissa et al [43], ovarian cysts and paraovarian cysts were also reported in higher frequency in she-camels.…”
supporting
confidence: 88%
See 3 more Smart Citations